Penerapan Pendekatan Kooperatif Talking Chips untuk Meningkatkan Partisipasi dan Hasil Belajar IPA Siswa Kelas IV - Nisa Lia Utami; Anis Fuadah Zuhri; Rohmat Widiyanto (Elementar : Jurnal Pendidikan Dasar, 2021)
This research aims to determine the application of the cooperative approach type talking chips in increasing participation and student learning outcomes in science learning in class IV B MI Nurul Islam Ciputat. This research was conducted in March 2020 in class IV B MI Nurul Islam Ciputat. The research method used was Classroom Action Learning (PTK) which was conducted in two cycles. The subject of this study consisted of 35 class IV B students of MI Nurul Islam Ciputat. The data collection techniques used werw observation, interview, test and documentation. The result showed that the was an improve in participation and student learning outcomes in cycle I and cycle II. The result of student activity observations showed an increase in student participation with an average percentage score of 72% with the good category in cycle I and increased to 83% in very good category in the second cycle. The result of the student learning test showed that the student obtained an average value of 72,94 with the complete category in the first cycle and increased to 81,88 with complete category in the second cycle. Based on the result of this study, it can be concluded that the application of the cooperative approach type talking chips can increase the participation and learning outcomes of class IV B student of MI Nurul Islam.Keywords: Talking Chips, Participation, Learning Outcome